The role of herbal medicines in health care quality and the related challenges - Razieh Mirzaeian; Farahnaz Sadoughi; Shahram Tahmasebian; Morteza Mojahedi (Shahrekord University of Medical Sciences, 2021)
In recent years, there has been a renewed interest in the use of herbal medicines. Quality control and safety are two critical principles to be considered in the production process of herbal medicines. This review study aimed to investigate the condition of the countries other than Iran in terms of observing the safety principles, quality control, and meeting the standard of herbal drug use. In this systematic review, references were selected using the search terms "health-care quality" and "challenges of herbal medicine usage" from the databases "Web of Science" and "PubMed" published between 2000 and 2019. To select the resources among the selected literature, confirmation was accomplished by two researchers and Cohen's kappa coefficient (κ). The selected papers were classified based on publication year, journal, country, reference standards, regulation, toxicity evaluation, quality control, efficacy, safety, and adverse effects in herbal medicine. From 1532 retrieved papers, 27 papers with an estimated Cohen's kappa coefficient of 0.81 were confirmed and included in the study. Based on the analysis, the main findings of the papers were thematically classified into seven subcategories as follows: reference standards in herbal medicine, regulation of herbal medicinal products, toxicity evaluation for herbal products, quality control of herbal medicine, efficacy, adverse effects of herbal medicine, and safety. Given the significance of the effects of herbal medicines on health care quality, it is essential to codify guidelines on the proper use of these drugs.